Localization and identification of visual targets in high and low AQ individuals during visual search - Tantyana Mohamed Rosli (2016)
Individuals with autism or possesses autistic characteristics are known to be superior in local processing while having normal-to-deficit global processing. Much research has been conducted to investigate such phenomenon. Yet, the definitions of local and global stimuli in different studies were not consistent. This study aims to clarify the experimental definitions of both local and global stimuli in visual search tasks and investigate if autistic traits affect performance in such visual search tasks when participants were asked to locate and identify the local and global visual targets. The study hypothesized that high autism quotient (AQ) individuals would have similar response time as low AQ individuals in the global visual search task but would be faster at local visual search task than the low AQ individuals. Additionally, the study predicted that high AQ individuals would not respond slower than low AQ individuals in localization of both local and global visual targets. All the hypotheses for this study were met except that the high AQ group did not show superior search abilities during the local visual search task. The high AQ group were not slower at global visual search. Interestingly, both groups were slower when searching for local visual targets as compared to global visual targets. High AQ individuals did show any impairment or slow response in localization task for both local and global visual search despite believed deficit in dorsal stream functioning. The implication of this study could look into studying the reasons behind the superior local processing abilities and the development of a new hybrid theory that consist of both weak central coherence and enhanced perceptual functioning theory.